The role of women’s farmer groups as an alternative solution to food insecurity during the covid -19 pandemic - Fisy Amalia; Eko Cahyo Mayndarto; Farhaan Priyadi; Jidan Dwilaksana; Khoirul Anam (Enrichment : Journal of Management, 2023)
This research was conducted to determine the management effectiveness of the Azzahra farmer women's group program in the Buaran area, South Tangerang, Indonesia, which was carried out from March 2021 to August 2021. The data taken are primary and secondary; primary data is taken from observations, documentation, and interviews with the chairwomanman, advisor, and group members. Secondary data are taken from a literature review. The results of the research conducted found that this group of farmer women has carried out management effectively to prevent food insecurity while improving their welfare by farming in groups. This is shown by the expansion of the cultivated land, which was originally only three hundred meters, to ten thousand meters with the addition of plant varieties, the improvement of the welfare of its members obtained from the purchase of cheap foodstuffs, and also the earning of wages from the sale of these crops. The group was also able to repay operational loans within two years. During the COVID-19 pandemic, they were able to donate part of the harvest to orphans in the surrounding area. The conclusion of this study is that the farmer women's group program can be used as a solution to prevent food insecurity in times of crisis.